Diagnosis Of Fetal Mortality In Ewes And The Time Of Occurrence Using Real- time B. mode Ultrasonography: H.M. AL-Rawi , S.N. Omran - AL-Rawi, H. M. (The Iraqi Journal of Veterinary Medicine, 2007)
The aim of this study was to diagnose fetal mortality and the time ofoccurrence using real-time ultrasonography. 118 ewes were included in thisexperiment, to synchronized estrus of 47 ewes were carried out by usingintravaginal sponges containing 40 mg progesterone for 14 days and theninjected intramuscularly with 500IU of eCG at the time of sponge withdrawal,while 71 ewes were not treated and left to cycling normally. All ewes weremated naturally. In order to determinate of fetal numbers and observing fetalmortality, ewes were examined by 5MHz real- time ultrasonography at interval20-24, 25-29, 30-34, 35-39 and after day 40 after breeding. The results showedthat embryonic mortality rate in non treated and in treated ewes were 21.4,45.7% respectively. A high embryonic mortality rate occurred in treated and nontreated ewes within 20-24 days of gestation. There was a positive correlationbetween embryonic number and embryonic mortality in treated ewes.